2015
DOI: 10.2147/dddt.s81998
|View full text |Cite
|
Sign up to set email alerts
|

Effect of database profile variation on drug safety assessment: an analysis of spontaneous adverse event reports of Japanese cases

Abstract: BackgroundThe use of a statistical approach to analyze cumulative adverse event (AE) reports has been encouraged by regulatory authorities. However, data variations affect statistical analyses (eg, signal detection). Further, differences in regulations, social issues, and health care systems can cause variations in AE data. The present study examined similarities and differences between two publicly available databases, ie, the Japanese Adverse Drug Event Report (JADER) database and the US Food and Drug Admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 11 publications
0
71
0
Order By: Relevance
“…The comparison study demonstrated distinct discrepancies in reported drugs, reported AEs, seriousness and average number of reported events per case, between the JADER and FAERS . Since differences can arise as a result of discrepancies in reporting rules and customs in each country such as reporters and reported AE terms, which are associated with regulations, the two databases showed different features . For example, SRS databases mostly depend on the compliance of pharmaceutical companies to report according to regulatory requirements.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The comparison study demonstrated distinct discrepancies in reported drugs, reported AEs, seriousness and average number of reported events per case, between the JADER and FAERS . Since differences can arise as a result of discrepancies in reporting rules and customs in each country such as reporters and reported AE terms, which are associated with regulations, the two databases showed different features . For example, SRS databases mostly depend on the compliance of pharmaceutical companies to report according to regulatory requirements.…”
Section: Discussionmentioning
confidence: 96%
“…For example, SRS databases mostly depend on the compliance of pharmaceutical companies to report according to regulatory requirements. US companies need to submit case reports of non‐serious AEs, but reporting of known non‐serious AEs is not mandatory for Japanese companies . Each company has its own operational rules for AE reports, which makes them impossible for researchers to validate the contents of SRS databases .…”
Section: Discussionmentioning
confidence: 99%
“…Nomura et al reported that there are differences in the reported numbers of AEs between the JADER and FAERS; however, the number of shared reports between JADER and FAERS is unknown. 22) Regional differences in drug prescriptions or genetic backgrounds might be responsible for the differences in AEs. 22) The number of reports published in the JADER database is larger than that recorded in the FAERS database.…”
Section: -16)mentioning
confidence: 99%
“…22) Regional differences in drug prescriptions or genetic backgrounds might be responsible for the differences in AEs. 22) The number of reports published in the JADER database is larger than that recorded in the FAERS database. Therefore, we evaluated the seasonal variation of DIP using a logistic regression model.…”
Section: -16)mentioning
confidence: 99%
“…Post-marketing AE-reporting databases are among the fundamental resources in pharmacovigilance [11]. Previous reports, including some in patients treated with TCZ, have focused on structured data elements, such as age, sex, and onset of disease [7,12,13].…”
Section: Introductionmentioning
confidence: 99%